Acute upper gastrointestinal mucosal lesions caused by COVID-19 infection: a case report - Ze Qi; Bing-Jie Yan; Ruo-Han Hu; Lei Li (Frontiers in Medicine)
BackgroundCOVID-19 enters human cells by binding its surface protein to angiotensin-converting enzyme 2 (ACE2) present in the host. ACE2 is expressed in various organ cells in the human body. Consequently, SARS-CoV-2 can invade gastrointestinal epithelial cells through ACE2, leading to the manifestation of gastrointestinal symptoms. However, the occurrence of gastrointestinal mucosal lesions and bleeding is rare.Case summaryA 34-year-old man with no previous medical history was hospitalized due to two weeks of nausea, hematemesis, and one week of fever. Gastroscopy showed widespread inflammation and necrotic tissue in the stomach, suggesting erosive hemorrhagic gastritis. Laboratory tests confirmed COVID-19 infection and blood hypercoagulability. After treatment, the patient was discharged. Follow-up gastroscopy showed mucosal lesion healing after recovery from COVID-19.ConclusionThe patient underwent endoscopy and pathological analysis. ACE2 immunohistochemistry was performed on the pathological tissues to investigate the cause of the lesions. After ruling out other possible factors, the final results indicated that the patient’s gastric mucosal lesion was caused by COVID-19 infection. This suggests that further research on COVID-19 should consider its gastrointestinal symptoms and diseases.